IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MENINGKATAN PEMAHAMAN DAN PENGAMALAM NILAI-NILAI AJARAN ISLAM PADA MASYARAKAT DESA SEPON KECAMATAN LAMASI KABUPATEN LUWU - Afdal; M. Ilham Muchtar; M.Amin Umar (Jurnal Riset Guru Indonesia, 2023)
This study aims to find out: 1) Implementation of Islamic Religious Education in increasing understanding and practice of Islamic values in Sepon Village, Lamasi District, Luwu Regency and 2) To determine the supporting and inhibiting factors of Islamic Religious Education in Sepon Village, Lamasi District, Luwu Regency.This research is a qualitative field research with data collection methods in the form of observation, interviews, and documentation. Data analysis techniques using qualitative analysis. The results of this study are: 1) The implementation of Islamic religious education in Sepon Village does not occur completely, only partially because in Islamic religious education one must first understand or have knowledge before practicing Islamic teachings 2) Islamic religious education in Sepon Village is influenced several supporting and inhibiting factors. Supporting factors, namely the existence of government support for religious activities such as recitation and the establishment of a religious assembly, whose orientation can help the community to understand and practice Islamic teachings, are two ways the government helps Sepon Village, Lamasi District in implementing Islam. Meanwhile, the inhibiting factor is the good condition of facilities from in terms of human resources, namely coaches or ustadz/ustadzah and buildings that are still lacking in being an obstacle to carrying out religious activities so that they affect people who are lacking in Islamic religious knowledge.